The boy Mir [videorecording (DVD)] : ten years in Afghanistan - Grabsky, Phil (Microcinema International, Inc. [distributor], 2010)
Tracks the irrepressible and lovable Mir from a naive eight-year-old to a fully grown adult. Over the decade, it not only is a journey that follows Mir as he journeys into early adulthood in one of the toughest places on earth, but it's a film that is unmatched in mirroring and revealing the vitally important story of modern Afghanistan.